The Prevalence and Determinants of Fusidic Acid Resistance Among Methicillin-Resistant Staphylococcus aureus Clinical Isolates in China - Zhao, Huilin; Wang, Xinyi; Wang, Bingjie; Xu, Yanlei; Rao, Lulin; Wan, Baoshan; Guo, Yinjuan; Wu, Xiaocui; Yu, Jingyi; Chen, Liang; Li, Meilan; Yu, Fangyou (Frontiers in Medicine, 2021)
The significant increase in resistance of methicillin-resistant Staphylococcus aureus (MRSA) to fusidic acid (FA) is a worrying public concern. However, the data on the prevalence of FA-resistant MRSA isolates in China is still limited. This study aims to investigate the prevalence of FA resistance and resistance determinants among MRSA isolates from six tertiary hospitals in different regions of China between 2016 and 2020. The antimicrobial susceptibility of MRSA isolates was performed by disk diffusion test and broth microdilution method. Whole-genome sequencing was conducted to evaluate the determinants of FA resistance and molecular characterization of FA-resistant MRSA isolates. In this study, a total of 74 (74/457, 16.2%) isolates were identified to be FA-resistant among 457 non-duplicate MRSA isolates. The prevalence of 74 FA-resistant isolates was as follows: Hubei (28/70, 40%), Shanghai (18/84, 21.4%), Jiangxi (7/58, 12.1%), Inner Mongolia Autonomous Region (6/38, 15.8%), Guangdong (12/112, 10.7%), and Sichuan (3/95, 3.2%). The mutations in fusA were present in 79.7% (59/74) of FA-resistant MRSA isolates, with 54 (54/74, 73%) having L461K mutation and conferring high-level resistance [Minimum Inhibitory Concentration (MIC)>128 μg/ml]. Acquired gene, fusB, with low-level resistance (MIC <16 μg/ml) was found in 20.3% (15/74) FA-resistant MRSA isolates. ST5-MRSA-II-t2460 was the most prevalence clone with high-level resistance, accounting for 51.4% (38/74), which was distributed in Hubei (24/28, 85.7%), Inner Mongolia Autonomous Region (4/6, 66.7%), Shanghai (7/18, 38.9%), and Guangdong (3/12, 25%). ST630-t4549 MRSA isolates with low-level resistance were the most common in Jiangxi (3/7, 42.9%) and Sichuan (2/3, 66.7%). In brief, the prevalence of FA resistance among MRSA isolates in China was relatively high with geographic differences. High-level FA resistance was associated mostly with fusA mutations, especially the L461K mutation, whereas fusB usually conferred the low-level resistance to FA. The spread of ST5-MRSA-II-t2460 clone with high-level resistance to FA contributed greatly to the increase of FA-resistant MRSA isolates in most regions, especially in Hubei.